Pengaruh Intellectual Capital dan Spiritual Capital terhadap Kinerja Keuangan UMKM (Studi Kasus Pempek Sentosa Palembang) - Comaria, Ya Rizki; Nafsiah, Siti Nurhayati; Trisninawati, Trisninawati (Universitas Batanghari Jambi, 2025)
This study aims to analyze the simultaneous influence of intellectual capital and spiritual capital on the financial performance of UMKM Pempek Sentosa Palembang. This study uses a quantitative method. The data collection techniques used are questionnaires and interviews with purposive sampling techniques. The study population was 100 respondents consisting of managers and employees of Pempek Sentosa Palembang and a sample of 50 people calculated using the Slovin formula. Data analysis techniques include descriptive statistics, data quality, classical assumption analysis, and hypothesis analysis. The results of this study indicate that simultaneously and partially there is a positive and significant influence between the variables of intellectual capital and spiritual capital on the financial performance of UMKM Pempek Sentosa Palembang;